A bibliometrics analysis and visualization study of TRPV1 channel - Gao, Ning; Li, Meng; Wang, Weiming; Liu, Zhen; Guo, Yufeng (Frontiers in Pharmacology, 2023)
Background: At the end of the 1990s, transient receptor potential vanilloid 1 (TRPV1) was first identified and cloned, serving as a key pain and heat sensor in humans. A large body of evidence have revealed its polymodal structure, complex function and wide-spread distribution, the specific mechanism of the ion channel remains unclear. Our goal here is to perform a bibliometric analysis and visualization study to present hotspots and trends in TRPV1 channel. Materials and Methods: TRPV1-related publications from inception to 2022 were retrieved from the Web of Science database. Excel, VOSviewer, and CiteSpace software were utilized for co-authorship, co-citation and co-occurrence analysis. Results: There were 9,113 publications included in the study, the number of publications increased rapidly after 1989, from 7 in 1990 to 373 in 2007, during which the number of citations per publication (CPP) also reached a peak in 2000 (CPP=106.52). A total of 1486 journals published TRPV1 articles, mainly belong to Q1 or Q2 divisions; The United States published the most articles (TP=3,080), followed by Japan (TP= 1,221), China (TP=1,217), and England (TP= 734); In recent years, the TRPV1-related research direction has been broaden to multiple fields related to inflammation, oxidative stress, and apoptosis; Keyword clustering refined the topic distributions and could be generalized as neuralgia, endogenous cannabinoid system, TRPV1 mediated airway hyperresponsiveness, involvement of apoptosis, TRPV1 antagonists as therapy targets. Conclusions: By conducting an exhaustive bibliographic search, this review refined the topic distributions and generalized as neuralgia, endogenous cannabinoid system, TRPV1 mediated airway hyperresponsiveness, involvement of apoptosis, TRPV1 antagonists as therapy targets. It is currently being clarified how exactly TRPV1 works as an ion channel, and much more in-depth basic research is needed in the future.